Sarkoma jaringan lunak regio humeri. Penanganan dengan amputasi lengan atas - Teguh Aryandono, Teguh Aryodono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
The management of soft tissue sarcoma of the extremities is very complicated, particularly if the tumor is large and has infiltrated into the deep structures. Forequarter amputation is still one best choice for either curative or palliative purposes, although this operation is very mutilated.This report is aimed at presenting the benefit of forequarter amputation in patients with soft tissue sarcomas in the humeri region. Two patients with extrasceletal myxoid chondrosarcoma and pleomorphic rhabdomyosarcoma in the humeri region were managed with forequarter amputation and neoadjuvant chemotherapy. The patients condition and quality of life were better after the amputation.Key Words : soft tissue sarcoma - forequarter amputation - neoadjuvant chemotherapy - extrasceletal myxoid chondrosarcoma - pleomorphic rhabdomyosarcoma